Participation of Iranian Stroke Patients in Life Areas: A Systematic Review Article - Sahar Ghahremani; Abolghasem Fallahzadeh Abarguei (Journal of Rehabilitation Sciences and Research, 2022)
Background: Stroke is considered a common and major problem in the field of healthcare because of its high prevalence and long-term disabilities. The mainaim of rehabilitation is to increase the participation of stroke patients in differentareas of life. The current study purposed to review the factors influencing theparticipation of Iranian stroke patients in life areas.Methods: Databases including ISI-Web of Knowledge, PubMed, Google Scholar,and Scopus were searched using keywords such as occupational therapy,participation, activities of daily living (ADL), instrumental activities of dailyliving (IADLs), work, play, leisure, education, social participation, sleep, andrest in combination with Iranian stroke patients and CVA. The quality of thestudies was evaluated using the PEDro scale. All papers reviewed in this studyconcerned factors influencing the participation of Iranian stroke patients andwere published from 2000-2020.Results: In total, 178 articles were identified as eligible for an Iranian strokestudy. Of these, 104 articles were discarded, and an additional 38 were removedbecause of repetition and duplication. After careful evaluation of the papers, 34were selected for final analysis. Most of the included studies concerned the ADLarea of participation (N=32), and the lowest number of articles were in the areasof play (N=1), sleep/rest (N=2), and health management (N=3).Conclusion: In Iran, researchers have not paid enough attention to theparticipation of stroke patients in areas of life. Most studies focus mainly onpatient’s performance components, such as sensory and motor skills.